Evaluation of Outdoor Thermal Comfort Between Internal and External Space of Circular Courtyard Building in Hot Humid Climate - Sia, Sau Yaw; Zakaria, Mohd Azuan (Recent Trends in Civil Engineering and Built Environment, 2024)
Global warming is a common issue that cause global climate change and affect thermal environment of building, even some courtyard building design is less effective gradually in thermal performance and lack of case study on this issue in hot-humid climate. This study is aimed to evaluate the outdoor thermal performance between the internal and external courtyards based on the objective and subjective assessment. Four environmental parameter sensor were set at internal and external courtyard to assess the thermal performance of circular courtyard. For the subjective assessment, questionnaire survey was performed and conducted simultaneously with physical field measurement on the case study location to obtain the thermal environment sensation from subjects. Comfort temperature was obtained and compared with the UTCI (Universal Thermal Climate Index) heat stress to evaluate the effectiveness of outdoor thermal performance between internal and external circular courtyard. The finding from this study is the comfort temperature of external courtyard is higher than internal courtyard by 0.5°C to 1.9°C, therefore internal courtyard is categorized as comfortable with moderate heat stress and the external courtyard is not comfortable with strong heat stress. These finding shows it can clearly to see the thermal performance of courtyard building design in hot humid climate and some improvement can be made in term of long-term time assessment for outdoor thermal comfort evaluation in future.